2012
DOI: 10.1177/1948550612436983
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice Concerns and Race-Based Attentional Bias

Abstract: The present study used eyetracking methodology to assess whether individuals high in external motivation (EM) to appear nonprejudiced exhibit an early bias in visual attention toward Black faces indicative of social threat perception. Drawing on previous work examining visual attention to socially threatening stimuli, the authors predicted that high-EM participants, but not lower-EM participants, would initially look toward Black faces and then subsequently direct their attention away from these faces. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 26 publications
6
50
0
1
Order By: Relevance
“…Although past research related to more general processing of ingroup and outgroup faces has demonstrated an attentional preference for Black over White faces in the early stages (Amodio et al, 2003;Bean et al, 2012;Trawalter et al, 2008), the present research concentrated on the extent to which participants focused on specific features when faces were presented for a more extended period of time. Even though this emphasis does not permit investigators to determine the specific psychological processes over time or to detect initial vigilance responses to threatening outgroup faces, it does allow them to better understand the importance of attentional patterns toward the face regions of ingroup and outgroup targets during person perception.…”
Section: Preferential Attention To the Eyes Of Ingroup Members 48mentioning
confidence: 93%
See 4 more Smart Citations
“…Although past research related to more general processing of ingroup and outgroup faces has demonstrated an attentional preference for Black over White faces in the early stages (Amodio et al, 2003;Bean et al, 2012;Trawalter et al, 2008), the present research concentrated on the extent to which participants focused on specific features when faces were presented for a more extended period of time. Even though this emphasis does not permit investigators to determine the specific psychological processes over time or to detect initial vigilance responses to threatening outgroup faces, it does allow them to better understand the importance of attentional patterns toward the face regions of ingroup and outgroup targets during person perception.…”
Section: Preferential Attention To the Eyes Of Ingroup Members 48mentioning
confidence: 93%
“…This decision to focus on a more extended period of time, however, has important implications for our ability to infer the timeline of specific early attentional vigilance or avoidance processes related to outgroups Although it is possible that if we restricted our focus to processes during a very short timeframe, we could find results indicative of an attentional preference for outgroups (Amodio et al, 2003;Bean et al, 2012;, we are not convinced that this would necessarily be the case. Rather, because our interest is specifically on attention to the eye region, and because eye gaze may reflect a desire to better know or connect with the target person (Baron-Cohen et al, 1997;Mason et al, 2005), even early visual stages may show an avoidance of rather than preference for outgroup eyes.…”
Section: Preferential Attention To the Eyes Of Ingroup Membersmentioning
confidence: 99%
See 3 more Smart Citations